Effects of corporate actions on market dynamics during the COVID-19 pandemic: An event study on the Indonesia Stock Exchange - Lubis, Tona Aurora; Fitriaty, Fitriaty; Sari, Novita; Firmansyah, Firmansyah; Ningsih, Maryati (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
The COVID-19 pandemic has precipitated unprecedented uncertainty within the stock market, eliciting adverse reactions within the capital market. This environment compelled companies to engage in corporate actions. This research aimed to develop a model assessing the impact of corporate actions during the COVID-19 pandemic on the Indonesia Stock Exchange. This study employed an event study methodology to analyze corporate actions from March 1 to March 30, 2021, identifying four key actions: Stock Splits, Pre-emptive Rights (Rights Issues), Partial Delisting, and Warrants. These corporate actions influenced various metrics, including the frequency of stock returns, actual returns, stock returns, and trading volume activity. The outcomes of these actions varied, presenting differences before and after their execution. The study's findings categorize the impact of corporate actions during the pandemic into two distinct groups: insignificant and significantly negative. This research contributes to understanding the ramifications of corporate decisions during periods of heightened market volatility, specifically within the context of the Indonesia Stock Exchange during the COVID-19 pandemic.